Efeito da aplicação pré-colheita de bioestimulante e espaçamento de plantio na produção, qualidade e conservaçao de melancia - Paula, Vericía Fernanda Sales de (2015)
Currently, the use of growth biostimulant in vegetable crops has been used by some producers of watermelon. However, its effective influence on yield and quality of watermelon is not well established. The main objective of this study was to evaluate the growth promoter preharvest application Crop Set® and planting spacing on quality and seedless watermelon conservation (hybrid Style) and seed (hybrid Quetzali). The experiments were conducted in the community of Pau Branco, Mossoró-RN, following the experimental randomized block design in a factorial 3 x 2, three spacing between plants (40, 45 and 50 cm), with and without application of Crop Set ®, with four replications. Harvesting occurred at 65 days after sowing for the two hybrid watermelons (Style) and (Quetzali), being evaluated in each plot (combination of factors), the number of total and the weight of the total fruit and productivity. The fruits of each plot were analyzed for mass loss (PM), pulp firmness (FP), soluble solids (SS), titratable acidity (AT), soluble solids / titratable acidity (SS/AT), pH and total soluble sugars (AST) in zero time and in the range of 14, 21 and 28 days of storage. The Style cultivar was stored in cooling chamber set at 10° C and 90% RH and the Quetzali cultivarwas stored at 20°C and 60% RH. In step laboratory, it was adopted a completely randomized design with split plot storage time with six replications. The data were submitted to analysis of variance with the aid of SISVAR program, and the significant variables were compared using the mean test and regression analysis. For the watermelon seedless 'Style', the biostimulant application and crop spacing promoted mass loss, soluble solids, SS/AT ratio and pH differentiate of fruits depending on the storage time. Application of Crop Set® did not favor the accumulation of SS in fruit on harvest, but during storage, the values of SS vary with the spacing and bioestimulant application. At 28 days, the pH of the fruit did not differ with the application of Crop Set® and crop spacing. The SS/AT of fruits increased during the storage period, regardless of biostimulant in all crop spacings. In contrast, the fruit AT and FP AT decreased during the storage period. The AST content of the fruit was not influenced by the Crop Set® application. But, at 28 days, the spacing of 40 cm provided fruit with lower AST content fruit. For the production characteristic, only the number of fruits per plant was affected by treatment, the largest number of fruits was evidenced in cultivation spacing of 50 cm with Crop Set® application. In the first harvest, 78% of fruit were picked. For watermelon with seed (Quetzali), the Crop Set® application, plant spacing and storage times made significant effect on mass loss, soluble solids, total soluble sugars and acidity of fruit. For production characteristics evaluated, only the average weight of fruits per plot was influenced by treatment, with heaviest fruits detected in 50 cm of spacing without Crop Set® application. The biostimulant application in all plant spacing resulted in fruit with higher mass loss during storage. The highest SS value was obtained in fruit provided of spacing of 50 cm without Crop Set® application. The Crop Set® application provided higher AST on cultivated fruits at spacing of 50 cm at 14 days of storage. Regardless of the Crop Set® application, the higher AT was verified in fruit at zero time, when cultivated at spacing of 50 cm, and decreased during storage. The FP decreased and the SS/AT ratio and pH of fruit increased during storage